2020
DOI: 10.1183/13993003.01945-2019
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnoea treatment and blood pressure: which phenotypes predict a response? A systematic review and meta-analysis

Abstract: The treatment for obstructive sleep apnoea (OSA) with continuous positive airway pressure (CPAP) or mandibular advancement devices (MADs) is associated with blood pressure (BP) reduction; however, the overall effect is modest. The aim of this systematic review and meta-analysis of randomised controlled trials (RCTs) comparing the effect of such treatments on BP was to identify subgroups of patients who respond best to treatment.The article search was performed in three different databases with specific search … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 84 publications
2
80
0
15
Order By: Relevance
“…Recent meta-analyses indicate a significant but small reduction in BP values in OSA patients treated with CPAP [65][66][67], with more evident effects on patients with resistant hypertension and on overnight BP values. This is interesting because the role of nocturnal BP in the development of cardiovascular diseases and its association with cardiovascular mortality and morbidity both in hypertensive patients and in the general population has been confirmed in several longitudinal and population studies [68]. In addition to higher baseline BP values, excessive daytime sleepiness and, in particular, increased treatment compliance are also associated with increased positive effects of CPAP treatment on BP [69,70].…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 90%
See 1 more Smart Citation
“…Recent meta-analyses indicate a significant but small reduction in BP values in OSA patients treated with CPAP [65][66][67], with more evident effects on patients with resistant hypertension and on overnight BP values. This is interesting because the role of nocturnal BP in the development of cardiovascular diseases and its association with cardiovascular mortality and morbidity both in hypertensive patients and in the general population has been confirmed in several longitudinal and population studies [68]. In addition to higher baseline BP values, excessive daytime sleepiness and, in particular, increased treatment compliance are also associated with increased positive effects of CPAP treatment on BP [69,70].…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 90%
“…Oral devices are indicated for the treatment of mild to moderate OSA and their effect on BP values is promising, similar to that obtained with CPAP according to some studies. Recently, a meta-analysis [68] A subgroup analysis showed that patients with higher BP values prior to treatment, patients < 60 years of age, and patients with higher hypoxic load were more likely to exhibit a more pronounced hypotensive effect in response to CPAP treatment.…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 99%
“…A better effect of CPAP was observed in the resistant hypertension subjects −5.40 mmHg and −3.86 mmHg respectively [ 75 ]. In the subjects with severe oxygen desaturations (SpO2 < 77%) with good CPAP adherence the reduction of systolic blood pressure was observed [ 76 ]. Severe desaturations but not AHI were associated with better hypotensive response of CPAP.…”
Section: Endothelial Function After Treatment With Cpap In Specific Subgroupsmentioning
confidence: 99%
“…It greatly improves objective indices of OSA (e.g., apnea-hypopnea index-AHI/hour), and has significant beneficial effects on symptoms including daytime sleepiness and quality of life [8]. There is also some evidence that CPAP has beneficial cardiovascular effects, with studies showing improvements in blood pressure [9][10][11]. However, the literature is inconsistent regarding the extent of potential cardiovascular benefit conferred by CPAP.…”
Section: Cpap As the First-line Treatmentmentioning
confidence: 99%